The Impact of ICT and Travel Behavior - Abdul Satar, Nurul Hasanah (Multidisciplinary Applied Research and Innovation, 2023)
People travel to various locations and times of the day to perform various activities. People have virtual access to a wide range of activities, appreciate to information and communication technology (ICT), which eliminates the need for physical travel and thus reduces traffic congestion. This paper investigated the extent to which Malaysian tourists’ dwellers participated in travel activities via mobile phone or internet, as well as the impact of ICT usage on activity and travel behaviour. To determine the relationship between ICT and observed travel patterns, structural equation models were developed. According to the model results, facilitating more leisure activities.